BARRIERS ENCOUNTERED BY ELDERLY INDIVIDUALS IN SEEKING DENTAL CARE SERVICES AMONG PATIENTS ATTENDING A TERTIARY CARE HOSPITAL IN WESTERN TAMIL NADU, INDIA: A MIXED-METHODS STUDY - S, Sriram Balaji; GM, sharavanan; C, Nithyapriya; S, jeevithan; k, ramkishore; G, Sankamitra; Rathinamoorthy, Ramesh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to identify the barriers which prevent the elderly population from seeking early dental care.As our population continues to age, the oral health of elderly individuals becomes an increasingly important aspect of their overall well-being. However, a myriad of barriers often stands in the way of older adults accessing adequate dental care. These barriers can have a profound impact on their oral health, quality of life, and even their systemic health. Understanding these obstacles is crucial for developing strategies to ensure that elderly individuals receive the dental care; they need to maintain good oral health and overall well-being in their later years. To address this concern, we conducted a study that aimed at identifying the barriers in seeking early dental care among the elderly population attending a tertiary care hospital in western Tamil Nadu, India. Methods: This mixed-methods study was done among 384 elderly adults and senior citizens who attended the dentistry outpatient department of a tertiary care center in Coimbatore, Western Tamil Nadu, India, after 5 days of onset of symptoms. A structured questionnaire was used to collect data. Results: When questioned about the barriers to seeking dental care, 65.2% did not visit doctor due to anxiety and 50% did not feel the need to meet the doctor on time. 41.4% mentioned that accessibility issues were the main reason for delayed treatment. 56% reported financial constraints for delayed visits to the hospital. Anxiety and fear are prevalent emotions associated with dental visits and procedures in verbatims followed by availability, accessibility, and need. Conclusion: By recognizing and actively addressing these barriers, we can strive toward a health-care system that ensures that elderly individuals receive the necessary oral health care; they need to maintain their well-being and an improved quality of life in their later years. In doing so, we not only enhance their oral health but also contribute to the broader goal of promoting healthier and happier aging.